The Linkage Between Entrepreneurship Education and Green Entrepreneurship: Understanding Student Readiness for Green Enterprises - Rachmawati, Sela; Sholekhah, Irmadatus (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2025)
Green Entrepreneurship has emerged as a form of awareness in building ecological, economic, and social sustainability amidst the issue of environmental degradation and an increase in the earth's temperature continuous rise in the earth's temperature. This study explores students' readiness for green entrepreneurship. Green entrepreneurship includes entrepreneurship education, perceived technological capability, commitment to the environment, university support for green entrepreneurship and green entrepreneurial behavior. This method used qualitative method with six participants interviewed. Data analyze with this research is listening recording Zoom, writing and coding data, data interpretation and validation through FGD. The findings revealed that the concept of entrepreneurship integrated with the green entrepreneurship curriculum stimulates students towards environmentally friendly business practices. Collaboration between academics, students, and green industry players will strengthen the practice of environmentally sound entrepreneurship and form a young generation that is ready to face global challenges with sustainable and responsible solutions. The green entrepreneurship education curriculum is dynamically updated to include ecological, social and economic aspects. Keywords: entrepreneurship education, green entrepreneurship, student readiness